ANMATH AL-TA’ALLUM LADA AL-THALABAH FI MAHARAH AL-KALAM BI JAMI’AH ANTASARI AL-ISLAMIYYAH AL-HUKUMIYYAH - Muradi, Ahmad; Harisca, Rodhy; Alkautsari, Syarimah; Oensyar, H. M. Kamil Ramma; Muin, Muhamad Fatkhul (Journal of Applied Transintegration Paradigm, 2021)
Abstract: This study presents a learning style that is preferred by students who graduated from salafi boarding school on kalam skills. The purpose of this study was to determine the preferred independent learning style in kalam skills in graduated from salafi boarding school in Arabic education study programs. This research is field research using case study method and explanation building analysis technique. Data collection uses observation and interview methods. The object of this study is the learning style of students graduating from salafi boarding school on kalam skills. The research subjects were one student from Mursyidul Amin Gambut and one student from Darus Salim boarding school Bati Bati which is now under Arabic Language Study Program. Based on the result of the study it can be concluded that the learning styles of students graduating from salafi boarding school have different learning style. However they have a tendency to learn using style that they like. The trend of kalam learning style that is liked by the first student is auditory learning style with affective and social language learning strategies in vocabulary development. Whereas the tendency of learning style favored by the second student is auditory learning style with affective and social strategies and through language learning steps through speaking.